Performance enhancement of the photovoltaic cells system by using the pneumatic routers - Jaber, Ayad Jasim (2021)
Solar photovoltaic modules are of immense benefits to ordinary people in terms of independent energy solutions and conventional fuel savings. However, due to the inherent drawback of lower efficiencies per unit area, these technologies adoption rates are very slow and face resistance from domestic consumers for widespread acceptance. Thus, solar photovoltaic thermal hybrid technology was suggested, producing electrical and thermal output from the same unit area. Unfortunately, the lower individual efficiencies of the PV/T collector compared to their individual technologies hinders the potential advantages of this hybrid technology. This is due to the low solar energy absorption and high thermal resistance between the PV cell and the cooling medium. This study aims to develop a novel photovoltaic thermal collector to evaluate PVT performance using three rib configurations with pneumatic guiding devices. This thereby reduced thermal resistance and improved performance using different angles to increase system efficiency and reduce thermal losses resulting from increased temperature. The channel was developed and designed in the new model in three phases to study the improvement of heat transfer. The first phase is to test the simulation of the pneumatic routers numbers in the ribs, while the second phase is to test the simulation of the ribs numbers in the channel. Simulation analysis was conducted using 3D simulation by ANSYS-Fluent software to determine the optimum design of configurations in terms of the airflow channel. The results best from the simulation test indicate that the PVT complex with seven polygons and five vectors was the best design. The simulation results are shown in a combined PVT efficiency of 70.86 % and electrical PVT efficiency of 11.22% with a mass flow rate of 0.17 kg/s and solar irradiance of 1000 W /m². In the third phase, three different angles were chosen for pneumatic routers tested experimentally to determine the best angle. All configurations were set and tested experimentally outdoor under the Iraq climatic conditions to ASHRAE standard at different air mass flow rates. Experimental results of a PV inboard consisting of pneumatic ribs and angle guides with highest daily performance and electrical and thermal efficiency at angle guides of 30 ° compared to 45 ° and 15 ° and an empty PVT collector tube at air mass flow rate of (0.08- 0.17) kg/s. A good agreement was obtained when the 3D simulation and experimental results were compared. It was the average difference in the outlet air temperatures obtained in the numerical and experimental results from 6.18 % to 6.47 % and of the electrical and thermal efficiency from 5.25 % to 6.37 % respectively